Penerapan Thinking Aloud Pair Problem Solving (Tapps) Setting Working Backward Pada Materi Belah Ketupat Untuk Meningkatkan Hasil Belajar Siswa - Ulum, Darul; Mukhlis, Akhmad; Lestari, Rina Puji (AS-SUNNIYYAH, 2024)
One common goal of learning mathematics junior high school students were included in the National Education Standards is that students have the competence to solve problems that include the ability to understand the problem , devised a mathematical model , solve the model , and interpret the obtained solution . This research is motivated by the low student math learning outcomes . This is because of the lack of creative educators in teaching mathematics so that math becomes fun. Based on those explanations, problem formulation in this research is 1)Is the application of Thinking Aloud Pair Problem Solving (TAPPS) setting working backward method into Rhombus topic able to improve learning activity of Class VII B students of MTs Miftahul Huda?; and 2) Is the application of Thinking Aloud Pair Problem Solving (TAPPS) setting working backward method into Rhombus topic able to improve learning result of Class VII B students of MTs Miftahul Huda. Meanwhile, the purpose of this research is 1) to find activity improvements of the students in the application of Thinking Aloud Pair Problem solving (TAPPS) setting working backward learning method into Rhombus topic in Class VII B MTs Miftahul Huda; 2) to find study result improvements after using Thinking Aloud Pair Problem solving (TAPPS) setting working backward method into Rhombus topic in Class VII B MTs Miftahul Huda. The research method is descriptive quantitative research method and classroom action research by data analysis technique. Based on this study result, students activity porcentage in first meeting was 87,5 % with ‘very active category’, while in second meeting the porcentage was 92,4 % with ‘very active category’. This result shows the improvement by 4,9%. Meanwhile, result analysis of students learning progress data based on data in Mathematics teacher, shows that comprehension porcentage of previous material reviews was 70,8 %, while comprehension porcentage of the last test is 87,5 %. It shows that there is improvement by 16,7 % in students comprehension at Mathematics and classically comprehensed. Based on research results and analysis, it can be concluded that 1) Aplication of TAPPS setting working backward is able to improve students activities in Class VII B MTs Miftahul Huda; and 2) Application of TAPPS setting working backward is able to improve study results of students in Class VII B MTs Miftahul Huda.